The mode of involvement and pattern of injury resulting from motorcycle road traffic accidents: data from a tertiary mission hospital in ogbomoso, nigeria - Durodola Adewumi Ojeniyi; Amole Isaac Olusayo; Adeniran Adenike; Awotunde Olufemi Timothy (International Journal of Medical Research and Review, 2015)
Background: The current increase in the use of motorcycles in Nigeria has been associated with an increased incident rate of motorcycle road traffic accidents (MRTAs). Mode of involvement in MRTA differs; either as Pedestrian, Motorcyclist or as Passenger or Pillion rider.Aim and Objectives: To determine the prevalence of MRTA, mode of participation and the types and severities of injuries sustained by all those involved.Material and Method: A prospective, hospital-based descriptive study was conducted between September 2005 and June 2006. Eligible patients that presented to the Emergency Department were enrolled as subjects. Data was recorded in a structured recording schedule and analyzed using SPSS 11. Proportions were determined and statistics presented in tables.Results : There were 72 riders (46.2%), 54 passengers (34.6%) and 30 pedestrians (19.2%) seen during the study period. MRTA incidence rate was 49.5%. The mean age was 34.33+16.48 years and students were most affected (21.2%). Sixty-six patients (42.3%) each had injuries involving one and two body regions while 21 patients (13.5%) had injuries involving three body regions. The most frequent injury severity score (ISS) was four (17.9%). ISS was ≥5 in 102 patients (65.4%). Passengers were more likely to have ISS <5 compared with riders and pedestrians. Injury to the left side occurred in 82.1% of the victims.Conclusion: Though injury pattern differs by mode of participation, injury severity was almost the same. More injuries occurred on the left side of the body and more passengers are likely to be injured on commercial motorcycles.